Case report: Three characteristics of tyrosine kinase inhibitor-associated cerebrovascular stenosis. High threshold for infarction, atypical infarct area, and vascular recoverability under the use of ponatinib - Hanazono, Akira; Abe, Masamichi; Togashi, Shuntaro; Takahashi, Teruko; Takahashi, Naoto; Sugawara, Masashiro (Frontiers in Stroke, 2024)
While tyrosine kinase inhibitors (TKI)-associated cerebral vascular stenosis (CVS) exhibit distinct mechanisms compared to conventional stroke in basic research, the clinical strategy remains nearly the same other than TKI-switching. We present the case of a 22-year-old female with chronic myeloid leukemia without stroke risk factors, who developed ponatinib-associated CVS. Three potential characteristics of TKI-associated CVS were identified: a heightened threshold for infarction, an atypical infarct area, and vascular recoverability. Specifically, brain computed tomography remained normal despite 20 hours of severe hemiplegia. The ischemic distribution was confined in gray matter and the anterior cerebral artery territory on magnetic resonance imaging, despite severe stenosis of the internal carotid artery. Ischemic changes resolved within 10 days and arterial stenosis improved after ponatinib withdrawal. These unique features, distinct from typical stroke, could lead to misdiagnosis as non-organic neurological disorders or other conditions in ponatinib-treated patients.